Towards The Quest To Reduce Income Inequality In Africa: Is There A Synergy Between Tourism Development And Governance? - Isaac K. Ofori; Toyo A. M. Dossou; Seyi S. Akadiri (Tourism, 2021)
Despite the growing attention on the tourism development-income inequality nexus, a conspicuous gap in the literature is that rigorous empirical works examining how good governance moderates the relationship is hard to find. Anchoring on the trickle-down theory and the tourism-led growth hypothesis, this study fills this void in the literature based on data for 48 African countries for the period 1996 – 2020. We provide strong evidence robust to several specifications from the GMM estimator to show that, though unconditionally both tourism development and governance reduce income inequality in Africa, the effect of the former is amplified in the presence of quality economic, political and institutional governance. Particularly, we find that control of corruption and political are keys for propelling Africa's tourism sector contribute to policymakers' quest of fostering shared prosperity in the continent. Policy recommendations are provided in line with SDG 10 and Aspiration 1 and 3 of Africa's Agenda 2063.
Keywords: C33; D31; D63; H11; L5; O55; Z32; 330; Africa; Corruption; Governance; Income Inequality; Tourism Development; Tourism Receipts